Integrasi Spiritualitas Islam dan Tradisi Kultural Tengger: Studi Etnografi tentang Harmoni Sosial Masyarakat Bromo - Ahmad Zubaidi; Sofiyatil Aliyah; M. Khusna Amal; Mursalim Mursalim; Halim Soebahar (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
This study aims to examine the forms of integration between Islamic spirituality and the cultural traditions of the Bromo community as a model of socio-religious harmony in a multicultural setting. Employing a qualitative approach with an ethnographic method, the study explores the social, symbolic, and spiritual values embedded in the religious and customary practices of the Bromo community, particularly among the Muslim Tengger group. Data were collected through participant observation, in-depth interviews with 12 key informants consisting of religious leaders, traditional leaders, and community members, as well as documentation of local traditions. The findings indicate that the integration of Islam and local culture operates through three main pillars: spiritual engagement, defined as the active participation of Muslim community members in local spiritual rituals and communal religious life; cultural negotiation, referring to the process of reinterpreting indigenous traditions to align with Islamic teachings; and communal harmony, which denotes patterns of social interaction based on cooperation and mutual respect across religious boundaries. Rituals such as Kasada and earth alms (sedekah bumi), historically rooted in pre-Islamic traditions, are practiced by Muslim Tengger communities through adjusted meanings as expressions of gratitude to Allah and as forms of cultural da‘wah. In everyday social life, Islamic values such as ukhuwah, ikhlas, and rahmah coexist with Tengger cultural values of rukun, tepo seliro, and ajining diri, as reflected in inclusive social relations oriented toward shared communal well-being. These findings describe a form of contextual spirituality that demonstrates the integration of religious values and local wisdom as a foundation for the practice of religious moderation in mountainous communities.